Prevalence of internet addiction amongst the IT professionals of Bangalore city and its effect on their lifestyle and dietary habits - M., Rohith; Patil, Shailaja S. (International Journal Of Community Medicine And Public Health, 2017)
Background: Internet is being widely used all around the world, had both positive and negative influence in human life. The number of users is increasing day by day. Recent reports indicated that some on-line users, particularly IT Professionals, were becoming addicted to the Internet in much the same way that others became addicted to drugs, alcohol, or gambling, which resulted in; reduced work performance, and even marital discord and separation. The objectives of the study were the pattern of Internet addiction on young’s internet addiction diagnostic questionnaire and the effects of Internet addiction on the lifestyle and dietary behaviour. Methods: Cross-sectional online survey was conducted amongst the IT Professionals of 4 different companies. Data was collected on a pre-designed questionnaire. The questionnaire consisted of 1. Socio-demographic information, 2.Young’s Internet Addiction Test (IAT) 3. Dietary pattern. The questionnaire was sent to 400 people through e-mail, out of which 353 subjects mailed back the questionnaire with complete response. Results: Majority of the participants were in the age group of 30 to 34, males and were educated up to post-graduate level. When the scores were tabulated on Young’s Internet Addiction Scale, 30.8% of the subjects were found to be mildly addicted to internet, where as 48.4% and 20.8% were moderately and severely addicted. Conclusions: People who are high in internet addiction are more likely to vulnerability to depression, anxiety, and stress. Psychological approach is essential to tackle this problem.